Pengujian Substantif Pengeluaran Kas Pada Puskesmas Kemiri Kabupaten Purworejo - Fatonah, Fatonah; Supriono, Supriono (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
The Community Health Center is a work unit of the Regional Public Service Agency (BLUD), which has the obligation to prepare financial reports based on Government Accounting Standards (SAP). The aim of this research is to detect the potential for material misstatements of cash disbursement at the Kemiri Community Health Center. The population in this study is cash disbursement transactions during February 2024, and there were 39 samples of official receipts. The data used in this research were the results of observations, interviews, questionnaires and sampling. The data analysis technique uses the cash disbursement audit technique namely sampling evidence of cash disbursement, checking sample completeness, examining the ledger, and drawing conclusions regarding the results of the compliance test. The results of substantive testing show that 64% of the cash disbursement receipt samples have met the criteria set by the author. The level of effectiveness of internal control is 95.2% indicating that internal control is very effective, but there are still weaknesses, namely that several supporting documents for cash disbursements are not complete, the goods/services purchase receipt does not have the "Paid" stamp, and there are several health workers whose job is to manage reports BLUD finances. Keywords: Substantive testing, internal control, cash disbursements.